(untitled) (The Pakistan Development Review, 1990)
This paper specifies a model to simultaneously estimate the price response, assuming an interdependence among crops. The model is applied to estimate ownand cross-price elasticities of five major crops in Pakistan, viz., wheat, cotton, rice, sugan:ane, and maize based on the production and expected wholesal price data for the period 1957-86. The study found little potential to· enhance overall agricultural productivity by ir.:reasing the single crop price, sillCe either the ownprice elasticities were low or, otherwise, the nagative cross-price effec ts on the production of other crops were high. However, a 100percent system at;; improv ment in terms of trade for agriculture will illCrease overall agricultural productivity by about 6 percent in the long run.